Seasonal Variation and Age Difference in Thermal Responses under Preferred Temperatures Determined by the Mothers - OHNAKA, Tadakatsu; TOCHIHARA, Yutaka; TSUZUKI-HAYAKAWA, Kazuyo (Journal of Home Economics of Japan, 1998)
Fourteen mothers along with their young children participated in this study to investigate the preferred temperatures, the seasonal variation in comfort levels, and thermophysiological responses. The test room temperature was preset at 25°C and was thereafter continually increased or decreased in increments of 0.4°C every minute. The direction of change was controllable by the mother subject who could achieve thermal comfort. The test duration was 40 min. While no significant differences were noted in the preferred and maximum temperatures between the summer and winter seasons, there are significantly seasonal differences in thermal sensation and physiological responses. The subjects reported that they felt cool during the summer experiments and warm during the winter experiments. The Tsk (mean skin temperature) for both the mothers and children were observed significantly higher in the summer than the winter under preferred temperatures. Also, thermal comfort and thermophysiological responses were compared at 25 t to investigate the age difference, menstrual cycle of the women, and sex difference of children between the summer and winter seasons. TS (thermal sensation) and CS (comfort sensation) in the summer were reported cooler and more comfortable than that in the winter at 25 °C. The Tsk of the children was observed significantly higher than that of the mother at 25°C.